The Tradition of Pasang Bagan (Kelong) in Laboh Village, Senayang District, Lingga Regency - Al Imran; Sri Wahyuni; Rahma Syafitri (Social Issues Quarterly, 2023)
The Post-Bauxite Mining Industry in Tembeling-Tanjung Village is managed by an ex-mining tradition, which is a copyrighted and human work of material objects, beliefs, delusions, events, or institutions inherited from one generation to the next, such as customs, arts, and property. This tradition is experienced by every member of the community as something that survives within a certain time. In this era, many traditions are still preserved in generations from ancestors to children and grandchildren in a society. Among the traditions still carried out and maintained by the people of Laboh Village, Senayang District, is the Pasang Bagan/Kelong tradition. This research aims to find out how the tradition of installing bagan/kelong in Laboh Village, Senayang District, Lingga Regency is carried out. The study uses a qualitative descriptive approach with primary data sources from interviews with informants, including traditional leaders, bagang handlers, and the implementing community, using purposive sampling technique. Data collection techniques include observation, interviews, and documentation. Based on the results, it can be seen how the tradition of installing bagan is carried out, where people who want to set up the bagan must ask the handler of the bagan for water and report it. During the process of setting up the bagan, the spell water that has been requested from the bagan handler must be cast on the old stake or the first stake to be caked. Media such as spell water from the bagan handler is an essential requirement in constructing bagan/kelong.